Effectiveness of rumoh gizi gampong and positive deviance in improving the nutritional status of toddlers in Aceh - Wirda Hayati; Nurhayati Nurhayati; Anita Anita (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Stunting is a chronic nutritional problem that is a priority to address because it can affect the quality of children. Fulfilling the nutritional needs of children under five through positive family habits, including through family improvement and Rumoh Gizi Gampong (RGG), can significantly reduce stunting rates. The purpose of the study was to identify the effectiveness of Rumoh Gampong Nutrition and positive deviance in efforts to improve the nutritional status of toddlers in Aceh, with a quasi experimental design conducted in Merduati village, Kutaradja sub-district, Banda Aceh with 50 samples (25 intervention groups and 25 controls) using purposive sampling technique carried out on October 15, 2020-15 January 2021. Data collection using questionnaires with interview techniques, food record documentation studies and weight measurements using Dacin and height using microtoise. Data processing with paired T test, the results showed a significant difference in the intervention group on how to fulfill toddler food (p = 0,000), food intake (p = 0,000), and nutritional status (p = 0,000), there were differences in how to fulfill food in the intervention and control groups (p = 0,00), there were differences in food intake in the intervention and control groups (p = 0,001) and there were differences in body weight in the intervention and control groups (p = 0,001). It is recommended to the head of the puskesmas to support the positive deviance program and Rumoh Gampong Nutrition for all posyandu in their working area.